Sintesis Bioplastik Ramah Lingkungan Berbasis Pati Biji Durian dengan Filler Selulosa Sabut Kelapa: Synthesis of Environmentally Friendly Bioplastic Based on Durian Seed Starter with Coconut Cellulose Filler - Ria Nurwidiyani; Ghufira; Nesbah; Deni Agus Triawan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Conventional plastic has become a concern because it is a problem for the environment. Bioplastics made from starch and natural polymers such as cellulose from coconut fiber can be a solution to these plastic problems. This study aims to synthesize and characterize bioplastics made from durian seed starch with sorbitol as a plasticizer and coconut coir cellulose as a filler. This research consisted of several stages of the procedure including the extraction of durian seed starch, isolation of coco coir cellulose, synthesis of bioplastics, and characterization of bioplastics. Bioplastics are made by the melt intercalation method. The resulting bioplastics were characterized by FTIR and mechanical tests (elastic modulus and tensile strength). In this study, the starch produced was characterized by a yellowish-white color and a rough texture with a yield of 10.95%. Before being used as a bioplastic filler, the coconut coir powder was bleached using H2O2 in a base condition to reduce the presence of lignin and hemicellulose. Based on the FTIR spectrum, the bleaching process was indicated by a decrease in the intensity of the absorption peak at wavenumbers of 1246 cm-1 and 1642 cm-1 which were characteristic absorptions for lignin and hemicellulose. The results of the mechanical test showed that the bioplastic composition with the highest tensile strength and modulus of elasticity was owned by bioplastic with 4% cellulose, namely 7.28 MPa and 0.73 MPa.